1977
DOI: 10.1111/j.1365-2818.1977.tb00059.x
|View full text |Cite
|
Sign up to set email alerts
|

Freeze‐fracture for scanning electron microscopy

Abstract: Two different freeze-fracture methods are explored for preparation of biological material for scanning electron microscopy. In the simpler method the tissues are first fixed and dehydrated. They are then frozen and fractured, and after thawing, critical-point dried. This method has already been used in a number of studies of animal tissues (heart, liver, kidney). It is applied here to the examination of plant material (leaf mesophyll cells). In the second method tissues, or cells, are first infiltrated with cr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
26
0

Year Published

1984
1984
2000
2000

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 48 publications
(26 citation statements)
references
References 1 publication
0
26
0
Order By: Relevance
“…It has well been confirmed that the substitution or infiltration of biological specimens with ethanol, DMSO, and other anti-crystal agents or solvents before freezefracture prevents ice crystal damage of tissues, and that this fracture using pure or absolute solvents almost always produces flat fracture surfaces without regard to cell boundaries (TANAKA and IINO, 1972;TOKUNAGA et al, 1974;HuMPIREYS et al, 1974;HAGGIS and PHIPPS-TODD, 1977). It has also been well confirmed that in the DMSO freeze-fracture, the fracture planes usually run along the nuclear and mitochondrial envelopes or between the outer and inner layers of these envelopes (TOKUNAGA et al, 1974).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It has well been confirmed that the substitution or infiltration of biological specimens with ethanol, DMSO, and other anti-crystal agents or solvents before freezefracture prevents ice crystal damage of tissues, and that this fracture using pure or absolute solvents almost always produces flat fracture surfaces without regard to cell boundaries (TANAKA and IINO, 1972;TOKUNAGA et al, 1974;HuMPIREYS et al, 1974;HAGGIS and PHIPPS-TODD, 1977). It has also been well confirmed that in the DMSO freeze-fracture, the fracture planes usually run along the nuclear and mitochondrial envelopes or between the outer and inner layers of these envelopes (TOKUNAGA et al, 1974).…”
Section: Discussionmentioning
confidence: 99%
“…This process was initially used in blood vascular casts (MURAKAMI, 1971) and then in animal and plant materials (TANAKA and IINO, 1972;HUMPHREYS et al, 1974;HAGGIS and PHiPPS-TODD, 1977). The freeze-fracture of conductively stained samples was initiated by FUJITA and his associates (TOKUNAGA et al, 1974).…”
Section: Discussionmentioning
confidence: 99%
“…Conventional SEM was applied to fish and human cerebellum using the ethanol-cryofracturing technique (Humpreys et al 1974) and the freeze-fracture method for SEM (Haggis and Phipps-Todd 1977), using Freon 22 cooled by liquid nitrogen, with minor modifications for application to the nerve tissue (Castejon 1993(Castejon , 1994.…”
Section: Confocal Laser Scanning Microscopy Andmentioning
confidence: 99%
“…In contrast, oocyte microvilli are thin and short. The"curly hair-like microvilli" of corona follicle cells and especially those terminating deep in the oocyte cytoplasm, besides being the expression of active exchange of nutrients, may serve to finely modulate oocyte maturation.The study of intracellular organelles by scanning electron microscopy (SEM) began about 20 years ago with the use of various cracking methods, including cryofracture and frozen resins (TANAKA, 1972;HAGGIS and PHIPPS-TODD, 1977). At that time, the utility of these techniques was quite limited in that the low resolution power of SEM rendered it impossible to remove the cell matrix embedding and masking the cellular structures.…”
mentioning
confidence: 99%
“…The study of intracellular organelles by scanning electron microscopy (SEM) began about 20 years ago with the use of various cracking methods, including cryofracture and frozen resins (TANAKA, 1972;HAGGIS and PHIPPS-TODD, 1977). At that time, the utility of these techniques was quite limited in that the low resolution power of SEM rendered it impossible to remove the cell matrix embedding and masking the cellular structures.…”
mentioning
confidence: 99%